Wild dark shore [large type] - McConaghy, Charlotte (Thorndike Press, a part of Gale, a Cengage Company, 2025)
"Dominic Salt and his three children are caretakers of Shearwater, a tiny island not far from Antarctica. Home to the world's largest seed bank, Shearwater was once full of researchers, but with sea levels rising, the Salts are now its final inhabitants. Until, during the worst storm the island has ever seen, a woman mysteriously washes ashore. Isolation has taken its toll on the Salts, but as they nurse the woman, Rowan, back to strength, it begins to feel like she might just be what they need. Rowan, long accustomed to protecting herself, starts imagining a future where she could belong to someone again. But Rowan isn't telling the whole truth about why she set out for Shearwater. And when she discovers sabotaged radios and a freshly dug grave, she realizes Dominic is keeping his own secrets. As the storms on Shearwater gather force, they all must decide if they can trust one another enough to protect the precious seeds in their care before it's too late--and if they can finally put the tragedies of the past behind them to create something new, together"--